Analysis of Instrument Quality for Measuring High School Students’ Conceptual Understanding of Global Warming - Mohd Khairul Nizam Syah; Parlindungan Sinaga; Dedi Sasmita; Lina Aviyanti; Rapi Alwi Azhar (Mataram University, 2026)
Conceptual understanding of global warming is essential for enabling students to explain environmental phenomena scientifically and apply physics concepts to real-world issues; therefore, a valid and reliable assessment instrument is needed. This study aimed to analyze the quality of a test instrument measuring high school students' conceptual understanding of global warming using the Rasch Model. A descriptive quantitative approach was employed involving 43 eleventh-grade students from a public high school in Bandung selected through purposive sampling. The instrument consisted of 20 multiple-choice items based on the Revised Bloom's Taxonomy at the C2 level. Data were analyzed using MINISTEP. The results showed that the instrument satisfied the unidimensionality assumption, with 50.9% raw variance explained by measures and 6.7% unexplained variance in the first contrast. Item fit analysis identified 9 highly suitable items, 7 suitable items, 1 less suitable item, and 3 unsuitable items. Reliability analysis yielded person reliability of 0.63, item reliability of 0.93, and Cronbach's alpha of 0.71. Therefore, the instrument is generally suitable for measuring students' conceptual understanding of global warming, although several items require revision